Structure-function analysis of the Drosophila retinal determination protein Dachshund. - Tavsanli, B.C.; Ostrin, E.J.; Burgess, H.K.; Middlebrooks, B.W.; Pham, T.A.; Mardon, G. (Developmental Biology, 2004)
Dachshund (Dac) is a highly conserved nuclear protein that is distantly related to the Ski/Sno family of corepressor proteins. In Drosophila, Dac is necessary and sufficient for eye development and, along with Eyeless (Ey), Sine oculis (So), and Eyes absent (Eya), forms the core of the retinal determination (RD) network. In vivo and in vitro experiments suggest that members of the RD network function together in one or more complexes to regulate the expression of downstream targets. For example, Dac and Eya synergize in vivo to induce ectopic eye formation and they physically interact through conserved domains. Dac contains two highly conserved domains, named DD1 and DD2, but no function has been assigned to either of them in an in vivo context. We performed structure-function studies to understand the relationship between the conserved domains of Dac and the rest of the protein and to determine the function of each domain during development. We show that only DD1 is essential for Dac function and while DD2 facilitates DD1, it is not absolutely essential in spite of more than 500 million years of conservation. Moreover, the physical interaction between Eya and DD2 is not required for the genetic synergy between the two proteins. Finally, we show that DD1 also plays a central role for nuclear localization of Dac.